ChemInform Abstract: Amine Protection/α‐Activation with the tert‐Butoxythiocarbonyl Group: Application to Azetidine Lithiation—Electrophilic Substitution. Issue 23 (June 2015) - Hodgson, David M.; Mortimer, Claire L.; McKenna, Jeffrey M.
Abstract The use of the long‐neglected tert‐butoxythiocarbonyl group (Bot) for the α‐lithiation of Bot‐azetidines is examined in the presence of non‐chiral and chiral ligands.